OKB, a novel family of brain-gut neuropeptides from insects - Sterkel, Marcos (2012)
In insects, neuropeptides play a central role in the control of most physiological processes. The knowledge and characterization of new neuropeptide families, is of interest on the fields of Genetics, Genomics, Neurobiology, Endocrinology and Evolution. This knowledge also provides the tools for the design of peptidomimetics, pseudopeptides or small molecules, capable of disrupting the physiological processes regulated by the signaling molecules and their receptors. This is a promising target for a novel generation of insecticides. Using database searches, mass spectrometry and RACE-PCR, we identified a neuropeptide precursor transcript encoding a new family of insect neuropeptides in the hemipteran Rhodnius prolixus. We named this precursor Orcokinin B, because is originated by the alternative splicing of the Orcokinin gen. EST and genomic data suggests that Orcokinin B is expressed in the nervous system and gut from several insect species, with the exception of Drosophila sp. (Diptera) and Acyirthosiphon pisum (Hemiptera). Mass spectrometry and RT-PCR confirmed the expression of Orcokinin B in brain and anterior midgut of R. prolixus. Furthermore, we identified orthologues of this new family of peptides in genomic and EST databases from Arachnids and Crustaceans.